Optimalisasi Komunikasi Politik Kepala Desa Laweyan dalam Pengembangan BUMDes: Studi Khusus Desa Laweyan Kecamatan Sumberasih Kabupaten Probolinggo - Fiky Yunus (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Political communication is a process of conveying political messages involving political actors, government, power, and various activities within the political system. As a branch of communication science, political communication focuses on how political messages are constructed, delivered, received, and interpreted by the public, as well as how these processes influence public opinion and political decision-making. In the context of this study, the optimization of the village head’s political communication in developing th Village-Owned Enterprise (BUMDes) can be seen through the policy directions undertaken, such as providing training for livestock farmers particularly goat farming and managing village deliberation meetings (musdes) that support the sustainability of BUMDes programs. This research employs a descriptive qualitative method conducted in Laweyan Village, Sumberasih Subdistrict, Probolinggo Regency, with data collected through observation, interviews, and documentation. Dan Nimmo’s political communication theory serves as the analytical framework. The findings indicate that the Laweyan Village Government consistently strives to improve the community’s economy through the development of BUMDes, particularly in the agricultural and livestock sectors. Innovations carried out by the village government and BUMDes management, especially within the goat farming unit, have significantly contributed to the progress and sustainability of the enterprise.